Athletic Scholarships as Contracts: Legal Ramifications for the University and Obligations of the Student-Athlete - Reed, Judy L. (My University, 1992)
Scholarships based on athletic ability are the principal method used by universities to attract student-athletes to their schools. The idea that athletic scholarships are contracts between student-athletes and universities has been argued in the court system on a limited basis. Selected court cases pertaining to athletic scholarships for athletic performance were reviewed, and the contractual obligation that exists for universities to educate student-athletes was considered.
Keywords: scholarships; employer/employee relationship; legal issues